Strategizing research and development investments in climate change adaptation for root, tuber and banana crops in the African Great Lakes Region: A spatial prioritisation and targeting framework. (October 2022) - Vandamme, Elke; Manners, Rhys; Adewopo, Julius; Thiele, Graham; Friedmann, Michael; Thornton, Philip
Abstract: CONTEXT: Given the significance of climate change impacts on farming communities, large investments are made by research and development actors, including farmers themselves, to adapt agricultural systems. A data-driven approach is required to guide these investments and maximize their impact. In the African Great Lakes Region (GLR), root, tuber and banana (RT&B) crops are a vital component of smallholder farming systems, but little is known about strategies to mitigate climate change impacts on these crops. OBJECTIVE: The objective of this study was to develop a spatial prioritisation and targeting framework based on the risk of climate-related impacts to guide research investments and prioritisation in CSA for RT&B crops in the GLR. METHODS: Climate change impact data on crop suitability were layered onto other spatially-explicit biophysical and socio-economic data to map clusters of homologous regions, called socio-agroeocological homologues (SAHs). The SAHs were defined by the risk of climate-related impacts, resulting from the interaction of hazards, exposure and vulnerability. The framework was applied to RT&B crops (banana, potato, cassava and sweetpotato) in the African GLR. Its utility was illustrated by elaborating adaptation scenarios for selected SAHs of one long-duration (banana) and one short-duration (potato) RT&B crop. RESULTS AND CONCLUSION: Four SAHs were identified for banana, potato and sweetpotato and five for cassava. For each crop, SAHs were prioritised for investment in climate change adaptation based on the level of risk of climate-related impacts. Scenario analysis showed that the introduction of drought-tolerant varieties would increase suitability for banana from 0.30 to 0.47 under baseline conditions and from 0.54 to 0.71 under future climates in a prioritised SAH with low to moderate suitability for typical varieties. For potato, the introduction of heat-tolerant genotypes, intercropping with legumes or the combination of both would allow compensating negative impacts of climate change on crop suitability in two SAHs representing important mid-altitude potato growing areas, from an average of −0.19 and −0.16 to an average of up to +0.25 and + 0.15 respectively. Scaling approaches should consider the difference in socio-economic conditions between the two SAHs. SIGNIFICANCE: We envision the framework to be useful for a diverse range of users throughout the innovation and scaling continuum to understand where climate change impacts are expected to be most severe, what type of innovations are needed to help farmers adapt, and how these innovations should be scaled to enable uptake by considering socio-economic drivers of adoption. Graphical abstract: Unlabelled Image Highlights: Data-driven approach to guide climate change adaptation for root, tuber and banana crops in the African Great Lakes Region Clusters of homologous regions (SAHs), defined by the risk of climate-related impacts, were developed Four SAHs were identified for each of banana, potato and sweetpotato and five for cassava. The potential of genetic and agronomic innovations for mitigating impacts in prioritised SAHs was demonstrated Spatial framework to prioritise and target interventions throughout the innovation and scaling continuum